Imine based chiral liquid crystals: Effect of varying the terminal substituent and orientation of ester linking unit - Karanlik, Gurkan; Ocak, Hale; Eran, Belkiz Bilgin (ELSEVIER, 2019)
New liquid crystalline compounds composed of three-benzene-ring molecular core comprising both the imine and ester linkage units, (S)-3,7-dimethyloctyloxy chiral unit at one of terminals and n-dodecyl/dodecyloxy group as other side chain have been synthesized and characterized to study the effect of varying terminal chains, the orientation of polar ester linking group and the presence of molecular chirality on mesophase properties of imine based calamitic compounds. The liquid crystalline properties of the compounds were investigated by differential scanning calorimetry, optical polarizing microscopy and electro-optic methods. As a result of the strong effect of chirality of (S)-3,7-dimethyloctyloxy chain, all Schiff bases (imines) exhibit enantiotropic chiral smectic C (SmC*), chiral nematic (N*) as well as SmX phase just below the SmC* phase and blue phase (BP) appearing monotropically. The SmC* phase shows ferroelectric switching behaviour with P-S values in the range 70-130 nC cm(-2). The alteration of the n-alkyl tail with an alkoxy chain gives rise to a significant increase up to 30 C in mesomorphic transitions. The change in the orientation of polar ester linking group has no effect on the type and sequence of observed LC phase. As compared with (S)-4-(3,7-dimethyloctyloxy)phenol based imine derivatives (7a, 7b), the chiral nematic (N*) mesophase temperature range of (S)-4-(3,7dimethyloctyloxy)benzoate based compounds (8a, 8b) significantly broadened. Additionally, a decrease on the phase transition temperatures occurred with regardless of introducing n-dodecyl/dodecyloxy group as side chains. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Schiff bases (imines); Calamitic liquid crystals; Chiral mesophases; Ferroelectric behaviour; BLUE PHASES; PALLADIUM(II) COMPLEXES; MESOMORPHIC BEHAVIOR; CROSS-OVER; ROD; METALLOMESOGENS; MOLECULES; POSITION; SERIES; TAIL; Chemistry; Physics